The Effect of Metabolic Profile on Leptin, Adiponectin, and hs-CRP in Children and Adolescents with Type 1 Diabetes - Maria Kaza; Charalampos Tsentidis; Elpis Vlachopapadopoulou; Irine-Ikbale Sakou; Spyridon Karanasios; George Mastorakos; Kyriaki Karavanaki (Children, 2022)
Adipokines are a superfamily of cell signaling proteins produced by the adipose tissue. This study’s purpose was to reveal the association of adipokines (leptin, adiponectin), hs-CRP, and IL-6 with well-known cardiovascular risk factors (lipid profile, diabetes control, obesity, physical activity) in children and adolescents with T1D. This cross-sectional study included 80 participants (36 boys) with T1D, aged (mean ± SD) 14.8 ± 3.4 years. Body Mass Index (BMI), metabolic profile, and level of physical activity were assessed (using pedometers) for evaluation of their effect on serum leptin, adiponectin, IL-6, and hs-CRP. Leptin levels were associated with BMI (beta = 0.184, p < 0.001), waist to hip ratio (beta = −2.017, p = 0.022), Low Density Lipoprotein-C (LDL-C) (beta = 0.021, p = 0.005), and fat mass (beta = 14.07, p < 0.001). Adiponectin was correlated with waist to height ratio (beta = 0.048, p = 0.006), ΒΜΙ (beta = −0.056, p = 0.005), and muscle mass (beta = −0.013, p = 0.020). Interestingly, hs-CRP was associated with weight (beta = 0.035, p < 0.001), ΒΜI (beta = 0.186, p < 0.001), fat mass (beta = 5.2859, p = 0.004), and muscle mass (beta = 0.027, p = 0.008). Multiple regression analysis of muscle mass unveiled associations with log hs-CRP (beta = −1.237, p = 0.014) and inverse IL−6 (beta = 18.57, p = 0.01). Finally, multiple regression models of fat mass unveiled associations with physical activity (7-day-total-step-count) (beta = −3.90 × 10−7, p = 0.027), Inverse IL-6 (beta = −0.1572, p = 0.009), and squared leptin (beta = 0.0077, p = 0.03). This study reports a positive association of leptin with LDL-C, BMI, fat mass, and hip circumference and a negative association of adiponectin with BMI and muscle mass. Finally, hs-CRP was associated with HbA1c, fat mass, and BMI. We propose that leptin, adiponectin, and hs-CRP could be used as prognostic indicators of cardiovascular risk in children with T1D.